2012
DOI: 10.1371/journal.pone.0038097
|View full text |Cite
|
Sign up to set email alerts
|

Human Genome-Wide RNAi Screen for Host Factors That Modulate Intracellular Salmonella Growth

Abstract: Salmonella enterica is a bacterial pathogen of humans that can proliferate within epithelial cells as well as professional phagocytes of the immune system. While much has been learned about the microbial genes that influence the infectious process through decades of intensive research, relatively little is known about the host factors that affect infection. We performed a genome-wide siRNA screen to identify host genes that Salmonella enterica serovar Typhimurium (S. typhimurium) utilizes to facilitate growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…A number of host targets have been identified that are known to modulate host microbicidal properties (11)(12)(13)(14)(15)(16). Among the host factors, NRs in particular have been shown to modulate host effector functions that are imperative for clearance or survival of intracellular bacteria and parasites, including Listeria monocytogenes, Salmonella typhimurium, Leishmania donovani, and M. tuberculosis (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…A number of host targets have been identified that are known to modulate host microbicidal properties (11)(12)(13)(14)(15)(16). Among the host factors, NRs in particular have been shown to modulate host effector functions that are imperative for clearance or survival of intracellular bacteria and parasites, including Listeria monocytogenes, Salmonella typhimurium, Leishmania donovani, and M. tuberculosis (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Furthermore, inhibition of Rab1 by either RNAi or expression of dominant negative Rab1 constructs indicate that Rab1 function is required for the survival/growth of L. pneumophila [189], C. burnetii [188], S. enterica Typhimurium [133,192], and Brucella melitensis [138]. Our data demonstrate for the first time that Y. pestis also belongs to this group.…”
Section: Rab1b Inhibition Results In Increased Acidification Of the Lmentioning
confidence: 64%
“…To date, there have been multiple genome-wide RNAi high-throughput screens to identify novel targets and pathways exploited by various bacterial and viral pathogens (Table 1-1; [130][131][132][133][134][135][136][137][138][139][140][141][142]). …”
Section: Rnai Screens Identify Novel Pathogenesis Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations